PEER TUTORING WITH XCHART UTILIZATION: ENHANCING STUDENTS' PROBLEM-SOLVING SKILLS AND SELF-DIRECTED LEARNING - Hanafiani, Lia Gatra; Nasrullah, Anton; Hidayat, Amat (Indonesian Journal of Teaching and Learning, 2023)
This study explores the effect of using XChart and applying peer tutoring to problem-solving abilities and student learning independence in mathematics education. The research method used is an experimental research design with a control group. The study results showed a significant increase in problem-solving abilities and students' learning independence in the experimental group compared to the control group. This study concludes that using XChart and applying peer tutoring can improve problem-solving abilities and student learning independence in mathematics education. This research's implications support using this combination in students' mathematics learning.